2022
DOI: 10.3390/pharmaceutics14050897
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and In Vitro/Vivo Evaluation of Drug Nanocrystals Self-Stabilized Pickering Emulsion for Oral Delivery of Quercetin

Abstract: The aim of this study was to develop a new drug nanocrystals self-stabilized Pickering emulsion (NSSPE) for improving oral bioavailability of quercetin (QT). Quercetin nanocrystal (QT–NC) was fabricated by high pressure homogenization method, and QT–NSSPE was then prepared by ultrasound method with QT–NC as solid particle stabilizer and optimized by Box-Behnken design. The optimized QT–NSSPE was characterized by fluorescence microscope (FM), scanning electron micrograph (SEM), X-ray diffraction (XRD), and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…As shown in Figure 4 A, the XRD spectra at 10–30° showed a series of sharp peaks, indicating the crystalline nature of quercetin. The typic peaks of the native quercetin are mainly at 2 of 6.3–7.3°, 10.8°, 12.5°, 13.6–14.3°, 15.7–18.0°, 24.4°, and 27.3°, which represented the crystalline part of quercetin [ 25 ]. Compared with the native quercetin, the quercetin particles obtained by antisolvent precipitation have the same diffraction peaks of 12.5°, 13.6–14.3°, 24.4°, and 27.3°, but have almost no diffraction peaks of 6.3–7.3°, 10.9°, and 15.7–18.0°.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 4 A, the XRD spectra at 10–30° showed a series of sharp peaks, indicating the crystalline nature of quercetin. The typic peaks of the native quercetin are mainly at 2 of 6.3–7.3°, 10.8°, 12.5°, 13.6–14.3°, 15.7–18.0°, 24.4°, and 27.3°, which represented the crystalline part of quercetin [ 25 ]. Compared with the native quercetin, the quercetin particles obtained by antisolvent precipitation have the same diffraction peaks of 12.5°, 13.6–14.3°, 24.4°, and 27.3°, but have almost no diffraction peaks of 6.3–7.3°, 10.9°, and 15.7–18.0°.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al found that puerarin nanocrystals obtained using high pressure homogenization can stabilize oil-in-water Pickering emulsions [ 24 ]. Wang et al reported that quercetin nanocrystals obtained by high pressure homogenization could be used for the stabilization of oil-in-water Pickering emulsions [ 25 ]. Silybin nanocrystals with 340 nm were also fabricated using high-pressure homogenization methods under >80 MPa [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, anti-solvent crystallisation method was used to develop quercetin nanocrystals by Li et al The prepared nanocrystals showed 24.6 ± 1.9 mV zeta potential, and enhanced bioavailability of quercetin [53]. Wang et al formulated quercetin nanocrystals using HPH method, and the developed quercetin nanocrystals showed 20.15% drug release, enhanced stability and therapeutic effect of quercetin [54].…”
Section: Quercetin Nanocrystalmentioning
confidence: 99%
“…A study was conducted on rats by Wang et al with a 50 mg kg −1 dose of quercetin encapsulated nanocrystal formulation. The result reported a higher plasma concentration of quercetin and enhanced bioavailability as compared to quercetin coarse powder suspension [54]. Ly et al evaluated the anti-cancer potential of quercetin-NPs by performing trials on female BALB/c nude mice.…”
Section: Pre-clinical Studies Conducted On Quercetin Nanoformulationsmentioning
confidence: 99%